Comparison of Metformin and Metformin Plus Liraglutide for Treating Metabolic Syndrome in Patients with Polycystic Ovarian Syndrome (PCOS) - Naz, Yousra; Setna, Zeryab; Banu, Sabiha; Maqsood, Asma (Indus Journal of Bioscience Research, 2025)
Background: This study compares the effectiveness of metformin (MET) monotherapy versus a combination of MET and liraglutide (LIRA) in managing metabolic syndrome in overweight women with polycystic ovary syndrome (PCOS), focusing on weight reduction and body mass index (BMI). Methods: A prospective cohort was conducted at Lady Dufferin Hospital, Karachi from April 2024 to Oct 2024, involving 70 women aged 18–40 years, diagnosed with PCOS based on Rotterdam criteria, and having a BMI ≥ 27.5 kg/m². Participants were randomly assigned into two groups: Group A received MET (1500 mg/day), and Group B received MET (1500 mg/day) plus LIRA (1.2 mg/day) for 12 weeks. Baseline and post-treatment outcomes, including weight, BMI, waist circumference, and lipid profiles, were analyzed. Results: Both treatment regimens significantly improved metabolic parameters. Group B demonstrated superior results with an average weight loss of 10.30 ± 1.30 kg and BMI reduction of 3.72 ± 0.67, compared to Group A’s weight loss of 5.99 ± 2.87 kg and BMI reduction of 2.24 ± 1.07 (p < 0.001). Improvements in triglyceride levels, HDL cholesterol, and waist circumference were more pronounced in Group B. However, no significant changes in hypertension parameters were observed in either group. Conclusion: The combination of MET and LIRA is more effective than MET monotherapy in managing metabolic syndrome in overweight PCOS patients. This dual therapy offers enhanced metabolic benefits, potentially improving both reproductive and overall health. Further long-term, multicenter studies are warranted to explore its broader impacts and sustainability.